2019
DOI: 10.1002/jcp.28419
|View full text |Cite
|
Sign up to set email alerts
|

Transient upregulation of TASK‐1 expression in the hypoglossal nucleus during chronic intermittent hypoxia is reduced by serotonin 2A receptor antagonist

Abstract: Hypoglossal motoneurons innervate genioglossus muscle, the contraction of which is critical in the maintenance of upper airway patency in patients with obstructive sleep apnea. As a potassium channel distributed in hypoglossal motoneurons, TWIK‐related acid‐sensitive K+ channel‐1 (TASK‐1) could be inhibited by 5‐HT. This study aimed to investigate if TASK‐1 expression in hypoglossal nucleus could be influenced by chronic intermittent hypoxia (CIH) and 5‐HT2A receptors antagonist. Two hundred twenty‐eight rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
(71 reference statements)
0
10
0
Order By: Relevance
“…These changes could also be mediated by the inhibitory effects of 5-HT and NA on TASK channels since noradrenergic and serotoninergic terminal density was increased in the HMN of rats submitted to CIH (Rukhadze et al 2010). On the other side, it was previously demonstrated that CIH increases TASK-1 protein expression in the HMN of rats, despite not identifying which type of hypoglossal motoneurones was affected (Li et al 2019). Therefore, additional experiments are needed to evaluate the expression of TASK-1 and TASK-3 in the protrudor and retractor hypoglossal motoneurones from rats submitted to CIH.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…These changes could also be mediated by the inhibitory effects of 5-HT and NA on TASK channels since noradrenergic and serotoninergic terminal density was increased in the HMN of rats submitted to CIH (Rukhadze et al 2010). On the other side, it was previously demonstrated that CIH increases TASK-1 protein expression in the HMN of rats, despite not identifying which type of hypoglossal motoneurones was affected (Li et al 2019). Therefore, additional experiments are needed to evaluate the expression of TASK-1 and TASK-3 in the protrudor and retractor hypoglossal motoneurones from rats submitted to CIH.…”
Section: Discussionmentioning
confidence: 96%
“…On the other side, it was previously demonstrated that CIH increases TASK‐1 protein expression in the HMN of rats, despite not identifying which type of hypoglossal motoneurones was affected (Li et al . 2019). Therefore, additional experiments are needed to evaluate the expression of TASK‐1 and TASK‐3 in the protrudor and retractor hypoglossal motoneurones from rats submitted to CIH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coordinates of RMg were 10.52-11.30 mm from the bregma in the midline and 10.4 mm below the dorsal surface of the skull according to the Paxinos and Watson atlas [22]. The procedure for guide cannula and the matched injection cannula implantation into the RMg region was described in previous studies [23].…”
Section: Surgerymentioning
confidence: 99%
“…In peripheral tissues, TASK-1 is also found in the carotid bodies, lung, heart, and pulmonary arterial smooth muscle [15][16][17] . Its expression throughout these tissues has therefore implicated TASK-1 in the control of breathing and also in sleep apnea 12,[18][19][20][21][22] . Furthermore, an X-ray crystal structure of the TASK-1 channel has recently been reported in complex with a compound class of TASK-1 inhibitors currently in clinical trials for the treatment of sleep apnea 23 .…”
Section: Introductionmentioning
confidence: 99%